Vitamin D and pancreas: The role of sunshine vitamin in the pathogenesis of diabetes mellitus and pancreatic cancer. Issue 16 (2nd November 2017) - Altieri, Barbara; Grant, William B.; Della Casa, Silvia; Orio, Francesco; Pontecorvi, Alfredo; Colao, Annamaria; Sarno, Gerardo; Muscogiuri, Giovanna
ABSTRACT: Increasing evidence suggests that vitamin D exerts multiple effects beyond bone and calcium metabolism. Vitamin D seems to play a role in pancreatic disease, including type 1 and type 2 diabetes mellitus as well as pancreatic cancer. Vitamin D's immune-modulatory action suggests that it could help prevent type 1 diabetes. In type 2 diabetes, vitamin D may influence β-cell function, insulin sensitivity, and systematic inflammation—all characteristic pathways of that disease. Data from observational studies correlated vitamin D deficiency with risk of type 1 and type 2 diabetes. Prospective and ecological studies of pancreatic cancer incidence generally support a beneficial effect of higher 25-hydroxyvitamin D concentration as well as inverse correlations between UVB dose or exposure and incidence and/or mortality rate of pancreatic cancer. This review discusses the literature regarding vitamin D's role in risk of diabetes and pancreatic cancer. The results to date generally satisfy Hill's criteria for causality regarding vitamin D and incidence of these pancreatic diseases. However, large randomized, blinded, prospective studies are required to more fully evaluate the potential therapeutic role of vitamin D in preventing pancreatic diseases.